Glutaric aciduria type 1: clinical, biochemical, neuroimaging and molecular findings in Iranian patients - Pirzadeh, Zahra; Tonekaboni, Seyed Hassan; Houshmand, Massoud; Nasiri, Jafar; Mollamohammadi, Mohsen; Sedighi, Mostafa; Aryani, Omid (Iranian Journal of Child Neurology, 2017)
Objective: Glutaric aciduria type 1 (GA1), is a rare, treatable neuro- metabolic disease, due to Glutaryl - CoA dehydrogenase (GCDH) gene mutation. More than 200 mutations in GCDH are reported. In regions without Neonatal blood screening (NBS), patients are diagnosed in symptomatic period. This study was the first report of clinical manifestation, neuroimaging and laboratory data including GCDH gene mutation in Iranian GA1 patients. Materials and Methods: In this cross-sectional, descriptive study, clinical manifestation, neuroimaging and metabolic finding of eleven Iranian GA1 patients were evaluated. GCDH mutations of patients were studied, too. Results: All of patients were diagnosed before 32 months old. Clinical presentation of GA1 includes acute encephalopathic crisis and / or developmental delay. Neuroimaging of patients were typical .We found three novel mutations in GCDH gene in Iranian GA1 patients. Two new mutations patients were low excretors of glutaric acid. There is no correlation of genotype and phenotype in our patients. Conclusion: Physician must remember GA1 in differential diagnosis of macrocephaly, developmental delay, acute encephalopathy, dystonia and dyskinesia. Early detection, proper treatment and selective screening of patients’ siblings can prevent neurologic disabilities.